Changes of Major Chemical Compositions During Industrial Fermentation of Domestic Cigar Tobacco and Comparative Analysis with Imported Cigar Leaves - Shen, Yanyuan; Hou, Bingqing; Zhao, Xianyan; Cao, Yang; Hu, Wenxiao; Xu, Jilei; Li, Zhixing; Hu, Yanqi; Qiu, Lei (Scientific Journal of Technology, 2025)
Chemical substances of tobacco raw materials are closely related to product style and aroma quality. In this experiment, the alkaloid content, amino acid content, non-volatile organic acids and aroma-causing substances of domestic cigar tobacco were dynamically tested by high performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS), and compared with those of Dominican cigar tobacco during the fermentation process. Under the proposed fermentation conditions, the alkaloid content of domestic cigar tobacco showed an overall decreasing trend, and the alkaloid content at the end of fermentation was lower than that of Dominican cigar tobacco, with a difference of 5.74%; the amino acid content at the end of fermentation was lower than that of the pre-fermentation by 90.60%, with a difference of 0.11% with that of the Dominican cigar tobacco; and the content of non-volatile organic acid was higher than that of the pre-fermentation by 20.74% at the end of fermentation, with a difference of 5.74% with that of the Dominican cigar tobacco. Dominican cigar leaf; carotenoid degradation products increased by 244.26% at the end of fermentation, which was not much different from Dominican cigar leaf; other aroma-causing products increased by 5.81% at the end of fermentation compared to pre-fermentation, which was 0.23% higher compared to Dominican cigar leaf.